EPIDEMIOLOGICAL TREND FOR LEPROSY IN MINAS GERAIS, 1995- 2015 - Karine Chaves Pereira (Cogitare Enfermagem, 2019)
Objective: To analyze the epidemiological leprosy trend in Minas Gerais from 1995 to 2015, focusing on grade-2 physical disability. Method: An ecological time series study, where the new cases of leprosy notified from 1995 to 2015 were selected. The epidemiological indicators were calculated by year of detection. The Prais-Winsten regression was used for trend analysis, with a 5% statistical significance. Results: 50,673 new leprosy cases were recorded in the state. There was a decreasing trend of the detection rates in the general population of -5.64; in children under 15 years old, it was -5.64; and with a grade-2 physical disability, it was -6.97. The proportion of new cases with grade-2 physical disability showed a steady trend. Conclusion: Endemic maintenance in Minas Gerais is evidenced with late detection and underreporting of cases, requiring greater investment in actions to eliminate and control the disease.